Using Transcranial Direct Current Stimulation to Treat Depression in HIV-Infected Persons: The Outcomes of a Feasibility Study - Knotkova, Helena; Rosedale, Mary; Strauss, Shiela M.; Horne, Jaclyn; Soto, Eliezer; Cruciani, Ricardo A.; Malaspina, Dolores; Malamud, Daniel (Frontiers in Psychiatry, 2012)
Transcranial direct current stimulation (tDCS) is a novel non-invasive neuromodulatory method that influences neuronal firing rates and activity on dopaminergic and serotoninergic circuits. TDCS has been shown to relieve Major Depressive Disorder (MDD) in the general population, suggesting its potential for other vulnerable -populations with high MDD prevalence. Aims: This study evaluated l feasibility, safety, acceptability and clinical outcomes of a two-week tDCS antidepressant treatment in HIV-MDD co-diagnosed patients, and the feasibility of collecting serum and saliva for analysis of immunity-biomarkers.. Methods: Ten enrolled patients underwent baseline evaluation and started the tDCS treatment (Mon-Fri for two weeks) delivered with Phoressor II 850 PM for 20 min at 2 mA at each visit, using 2 electrodes (36cm2 ) placed over F3 position of EEG 10-20 system and the contralateral supraorbital region. Outcome-measures were collected at baseline, after the last tDCS and two weeks later. A quantitative microarray (Ray Bio Tech Inc) for TH1/TH2 cytokines was used for saliva and blood analysis. Results: Analyzable outcome-data were obtained from 8 subjects. Depression scores significantly decreased (p<.0005) after the treatment. No serious adverse events occurred. Several transient minor AEs and occasional changes of blood pressure and heart rate were noted. Mini-mental status scores remained unchanged or increased after the treatment. All subjects were highly satisfied with the protocol and treatment results and described the desire to find new treatments for HIV-MDD as motivating participation. Conclusions: F indings support feasibility and clinical potential of tDCS for HIV-MDD patients, and justify larger-sample, sham-controlled trials.